Cost-Effectiveness of an Advance Notification Letter to Increase Colorectal Cancer Screening - Cronin, P.; Goodall, S.; O'Keefe, C.; Lockett, T.; Norman, Richard; Church, J. (Cambridge University Press, 2013)
Objectives: The aim of this study is to evaluate the cost-effectiveness of a patient-direct mailed advance notification letter on participants of a National Bowel Cancer Screening Program (NBCSP) in Australia, which was launched in August 2006 and offers free fecal occult blood testing to all Australians turning 50, 55, or 65 years of age in any given year.Methods: This study followed a hypothetical cohort of 50-year-old, 55-year-old, and 65-year-old patients undergoing fecal occult blood test (FOBT) screening through a decision analytic Markov model. The intervention compared two strategies: (i) advance letter, NBCSP, and FOBT compared with (ii) NBCSP and FOBT. The main outcome measures were life-years gained (LYG), quality-adjusted life-years (QALYs) gained and incremental cost-effectiveness ratio.Results: An advance notification screening letter would yield an additional 54 per 100,000 colorectal cancer deaths avoided compared with no letter. The estimated cost-effectiveness was $3,976 per LYG and $6,976 per QALY gained.Conclusions: An advance notification letter in the NBCSP may have a significant impact on LYG and cancer deaths avoided. It is cost-effective and offers a feasible strategy that could be rolled out across other screening program at an acceptable cost.